JENIS DAN MORFOLOGI VEKTOR FILARIASIS ASAL KABUPATEN MALAKA - Diana A. Wuri; Julianty Almet; Felsiatri Agnesia Jedaut (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
Filariasis is a chronic infectious disease caused by the filarial worms of the class of nematodes that is transmitted through mosquito bites. In its development, there are more than 23 species of filariasis vector consisting of the genus Anopheles. Culex sp. Aedes sp. Mansonia sp. and Armigeres sp. losses caused by filariasis is caused permanent disability beupa enlargement of legs, arms, genitals and breasts. This study aims to determine the type and origin of the district filariasis vector morphology of Malaka. Methodon This research includes the collection of samples carried out in Malaka Tengah sub-district and District Weliman, followed by maintenance of mosquito larvae into adults as well as identification of the type and morphology of mosquitoes by identifying key WRBU and the Department of Health (2008b), The results showed that the type of filariasis vector origin of Malacca District consists of two species of the Anopheles sp.and Culex sp. Anopheles sp. Have proboscis same morphological features with palpi long, scaly wing venation, slender abdomen, the head of the body there are antennas and the color of chocolate, and Culex sp. have morphological features blackish brown body, blunt abdominal tip, palpi shorter than the proboscis and dark wings with long narrow scales.